Stepping forward: Personality traits, choice of profession, and the decision to become self-employed - Michael Fritsch; Alina Sorgner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We argue that entrepreneurial choice proceeds in at least in two steps, with vocational choice nearly always preceding choice of employment status, whether that be self-employment or dependent employment. Since the two decisions are interrelated, analysis of entrepreneurial choice as a single act may lead to inconsistent estimates of the factors that determine the decision to launch a business venture. Our empirical analysis utilizes a bivariate probit model that jointly estimates both decisions. The results support our argument that entrepreneurial choice is a two-stage decision process.
Keywords: L26; J24; D01; 330; entrepreneurial choice; personality traits; vocational choice